(untitled) (Research, Society and Development, 2022)
This is a research about the interfaces between handicrafts, culture, tourism and development, considering the sociotechnical processes of an artisans association that have banana culture as the main source of raw material. The goal is to demonstrate the roles and influences of human and non-human actors in the composition of the socio-technical network, elucidating the socio-political dimensions in the constitution of organizational practices and processes, as well as their respective consequences with regard to different perspectives of development, from understanding that it should not be associated only with economic guidelines. From this approach, it was envisaged to point out possibilities for social changes from the associative artisan experience. The theoretical-methodological proposal is structured from the assumptions of the Actor-Network Theory and the Cartography of Controversies, which provides a background capable of elucidating how social reality is formed from the action of human and non-human actors and to demonstrate how processes composition of a social reality is constituted through different interests. The research points to the complexity and multidimensionality in the composition of the artisans association as well as to possible alternative paths with regard to the development of artifacts production practices and processes, when these are thought beyond strictly economic guidelines.